Buckling and postbuckling of single‐walled carbon nanotubes based on a nonlocal Timoshenko beam model. Issue 9 (20th May 2014) - Ansari, R.; Faghih Shojaei, M.; Mohammadi, V.; Gholami, R.; Rouhi, H.
<x xml:space="preserve">Abstract</x> In this research, the axial buckling and postbuckling configurations of single‐walled carbon nanotubes (SWCNTs) under different types of end conditions are investigated based on an efficient numerical approach. The effects of transverse shear deformation and rotary inertia are taken into account using the Timoshenko beam theory. The nonlinear governing equations and associated boundary conditions are derived by the virtual displacements principle and then discretized via the generalized differential quadrature method. The small scale effect is incorporated into the model through Eringen's nonlocal elasticity.